Development of conceptual provisions for investment support of balanced socio-economic development of the region - Stepanets, Ivan; Shafiieva, Leila (Technology audit and production reserves, 2021)
The object of research is the organizational-economic and organizational-managerial relations that arise in the process of managing investment processes in the region. One of the most problematic places is insufficiently disclosed issues on the theoretical and methodological platform for investment support of balanced socio-economic development of the region. The paper is based on theoretical and methodological provisions concerning the development of a promising regional strategy for investment development, taking into account the world scientific experience and effective management practice, and the study of the problems of investment development of the regional economy. The study used the method of monographic analysis and comparison to develop a conceptual and categorical apparatus of «regional strategy». Methods of scientific analysis, synthesis and analogies were used to study the development of a promising regional strategy for investment development. And the historical-logical method was used to determine the strategy as a method of setting long-term goals of the organization, its program of actions and priority areas for the allocation of resources. The research result was a content analysis of the content of the definition of «strategy» and «investment strategy». The investment strategy is interpreted as a general direction (program, plan) of investment activities in the region, the passage of which in the long run should lead to the achievement of investment goals and the expected economic effect. An important aspect in the organization of the investment process in the region is determined by the organizational and economic mechanism that regulates the behavior of agents engaged in investment activities. Conceptual provisions of investment support of balanced social and economic development of the region are formed. The author's vision of the investment strategy of the region allows to supplement and clarify its substantive aspects from the standpoint of considering this category as a long-term, high-quality process of providing the region with investment resources in order to achieve sustainable balanced development. The research results may be interesting in the further development and addition of theoretical provisions, methods and procedures that contribute to the study of areas and means of investment for balanced socio-economic development of the region.